Научный интеллект социологии - Тарасенко, В. (Социология: теория, методы, маркетинг, 2008)
The article explores the scientific intellect of sociology, as well as analyses its structural and functional content. The author has paid special attention to the interrelation between social and sociological ways of thinking.